اسلام میں حقوق و فرائض کی اہمیت: عدمِ ادائیگی کے معاصر رجحانات، رہنماپہلو: The importance of rights and duties in Islam and Contemporary trends in non-payment and guiding aspects - Habibullah; Muhammad Ashfaq khan; Usman Afaq (Al Manhal Research Journal, 2023)
As a blessing from Allah Almighty, children bring psychological peace to their parents. The emotions of compassion and love for children are natural in human beings. Man wants his name to continue through his children. He considers them as the rightful heir of his property and resources. Islam does not consider this sentiment wrong. He has kept it up and encouraged the progeny. Parents want their children to be highly educated and responsible, who will later become a source of good name for their parents. They should not be burden on anyone financially. When weakness and old age surround them, these children should bear their financial burden and be their support. Non-payment of rights trends are also found in the contemporary society. The guidelines are set from the following lines so that the society is built in the right direction.